2019
DOI: 10.1073/pnas.1907732116
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the interface mechanics of hard films and soft substrates for 3D assembly by controlled buckling

Abstract: Techniques for forming sophisticated, 3D mesostructures in advanced, functional materials are of rapidly growing interest, owing to their potential uses across a broad range of fundamental and applied areas of application. Recently developed approaches to 3D assembly that rely on controlled buckling mechanics serve as versatile routes to 3D mesostructures in a diverse range of high-quality materials and length scales of relevance for 3D microsystems with unusual function and/or enhanced performance. Nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…silicon wafers. On the other hand, a vertical wavy structure of metal interconnects with substrate wrinkling has been developed for high‐density wiring . Since the wavy structure is formed in the vertical direction with respect to an electrode substrate, a large number of electrodes can be patterned on the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…silicon wafers. On the other hand, a vertical wavy structure of metal interconnects with substrate wrinkling has been developed for high‐density wiring . Since the wavy structure is formed in the vertical direction with respect to an electrode substrate, a large number of electrodes can be patterned on the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a vertical wavy structure of metal interconnects with substrate wrinkling has been developed for high-density wiring. [30][31][32][33][34][35] Since the wavy structure is formed in the vertical direction with respect to an electrode substrate, a large number of electrodes can be patterned on the substrate. Previous studies have reported that to form a vertical wave shape, patterned electrodes can be attached to a prestretched rubber substrate that become wrinkled when the rubber returns to its natural state, [31][32][33] while In and Out of plain wrinkled electrodes have been developed for improving their stretchability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the compatibility with the well-established planar fabrication technologies, this approach can achieve high-speed, parallel assembly of 3D mesostructures with a broad range of thin-film materials and feature sizes, thereby paving the way to the development of novel micro-devices [7,[33][34][35][36]. Recent progress showed that strategic designs of 2D precursor structures [28,29,37] and deformable substrates [38][39][40] as well as the integration schemes [41][42][43][44] can substantially enrich the accessible range of 3D topologies. For example, the structured elastomer substrates with kirigami designs can introduce local rotational motions of the bonding sites to enable the formation of structures with chiral features and morphable shapes [39].…”
Section: Introductionmentioning
confidence: 99%